2021
DOI: 10.2188/jea.je20200185
|View full text |Cite
|
Sign up to set email alerts
|

Are Japanese Women Less Physically Active Than Men? Findings From the DOSANCO Health Study

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
3
10
0
Order By: Relevance
“…Similar findings were observed for both workers and nonworkers, although the degree of gender difference differed slightly by working status. This study among middle-aged adults in Japan confirmed the generalizability of our previous findings, 21,22 which showed older Japanese women were more physically active than older men. Our finding that women spent more time in PA of lower intensity is also consistent with those of previous accelerometer studies conducted in Western countries.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar findings were observed for both workers and nonworkers, although the degree of gender difference differed slightly by working status. This study among middle-aged adults in Japan confirmed the generalizability of our previous findings, 21,22 which showed older Japanese women were more physically active than older men. Our finding that women spent more time in PA of lower intensity is also consistent with those of previous accelerometer studies conducted in Western countries.…”
Section: Discussionsupporting
confidence: 90%
“…21 Moreover, a study among Japanese adults living in rural areas yielded similar results after taking into consideration the codependence of time-use components. 22 However, the generalizability of previous findings to middle-aged adults living in urban or regional cities-where the lifestyle and PA levels differ from those in rural areas- 8,23,24 remains unclear.…”
mentioning
confidence: 89%
“…Gender differences of activity patterns were in line with our previous findings [35,36] that Japanese older women were more physically active than older men, provided that all activity behaviors were assessed. In this sample, men experienced greater seasonal activity declines than did women.…”
Section: Discussionsupporting
confidence: 89%
“…OMRON accelerometer (HJA-750C) is one of Japan’s most popular validated triaxial accelerometer activity monitoring devices [ 12 , 13 ] that accurately measures the frequency, intensity, and duration of PA [ 14 ]. This device was worn on the waist, and METs data were collected in 60-sec intervals.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the OMRON triaxial accelerometer (HJA-750C, OMRON Healthcare, Kyoto, Japan) is widely used in the study of PA [ 12 , 13 ], and the validity of its metabolic equivalents (METs) estimation has been confirmed using the Douglas bag method [ 14 ]. OMRON has a proprietary algorithm for estimating METs every 60 s using a built-in triaxial accelerometer directly as raw data.…”
Section: Introductionmentioning
confidence: 99%